Could be a poet too little but so important? Mikhailo Petrenko in interpretation of Yuriy Shevelev (Sherekh) - Михайлин, Ігор Леонідович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article is considered the studio of Yuriy Shevelev "Another romantic, another romanticism" (1966) about M. Petrenko. The four aspects of M. Petrenko’s importance are established: 1) in Shevchenko times he was not an imitator of Shevchenko and developed personal-psychological trend in Ukrainian romanticism; 2) unlike Shevchenko’s specific vocabulary M. Petrenko contributed to the development of generic names, cultivated "zahalnykoviy" romanticism; 3) the folklore specific of M. Petrenko was that he refused ballade and song creation and brought the genres like romance, elegies, meditation; 4) his work challenged "kotlyarevschyna" and replaced high classical genres.